Reduced graphene oxide supported C3N4 nanoflakes and quantum dots as metal-free catalysts for visible light assisted CO2 reduction - Rakibuddin, Md; Kim, Haekyoung (Beilstein Journal of Nanotechnology, 2019)
The visible light photocatalytic reduction of CO2 to fuel is crucial for the sustainable development of energy resources. In our present work, we report the synthesis of novel reduced graphene oxide (rGO)-supported C3N4 nanoflake (NF) and quantum dot (QD) hybrid materials (GCN) for visible light induced reduction of CO2. The C3N4 NFs and QDs are prepared by acid treatment of C3N4 nanosheets followed by ultrasonication and hydrothermal heating at 130–190 °C for 5−20 h. It is observed that hydrothermal exposure of acid-treated graphitic carbon nitride (g-C3N4) nanosheets at low temperature generated larger NFs, whereas QDs are formed at higher temperatures. The formation of GCN hybrid materials was confirmed by powder X-ray diffraction, X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, field emission scanning electron microscopy, transmission electron microscopy (TEM), and UV–vis spectroscopy. High-resolution TEM images clearly show that C3N4 QDs (average diameter of 2–3 nm) and NFs (≈20–45 nm) are distributed on the rGO surface within the GCN hybrid material. Among the as-prepared GCN hybrid materials, GCN-5 QDs exhibit excellent CO2 reductive activity for the generation of formaldehyde, HCHO (10.3 mmol h−1 g−1). Therefore, utilization of metal-free carbon-based GCN hybrid materials could be very promising for CO2 photoreduction because of their excellent activity and environmental sustainability.
Keywords: CO2 reduction; metal-free hybrid; nanoflakes; photocatalyst; quantum dots

(untitled) - Xiang, Q.; Cheng, B.; Yu, J. (Angew. Chem., Int. Ed., 2015)

(untitled) - Tu, W.; Zhou, Y.; Zou, Z. (Adv. Mater. (Weinheim, Ger.), 2014)

(untitled) - Hamdy, M. S.; Amrollahi, R.; Sinev, I.; Mei, B.; Mul, G. (J. Am. Chem. Soc., 2014)

(untitled) - Kumar, S.; Kumar, A.; Bahuguna, A.; Sharma, V.; Krishnan, V. (Beilstein J. Nanotechnol., 2017)

(untitled) - Huang, X.; Wang, J.; Li, T.; Wang, J.; Xu, M.; Yu, W.; El Abed, A.; Zhang, X. (Beilstein J. Nanotechnol., 2018)

(untitled) - Chen, X.; Li, N.; Kong, Z.; Ong, W.-J.; Zhao, X. (Mater. Horiz., 2018)

(untitled) - Low, J.; Cheng, B.; Yu, J. (Appl. Surf. Sci., 2017)

(untitled) - Xin, C.; Hu, M.; Wang, K.; Wang, X. (Langmuir, 2017)

(untitled) - Wang, L.; Wang, Y.; Cheng, Y.; Liu, Z.; Guo, Q.; Ha, M. N.; Zhao, Z. (J. Mater. Chem. A, 2016)

(untitled) - Wang, S.; Wang, X. (Appl. Catal., B, 2015)

(untitled) - Neaţu, Ş.; Maciá-Agulló, J. A.; Concepción, P.; Garcia, H. (J. Am. Chem. Soc., 2014)

(untitled) - Sun, Z.; Wang, H.; Wu, Z.; Wang, L. (Catal. Today, 2018)

(untitled) - Ye, S.; Wang, R.; Wu, M.-Z.; Yuan, Y.-P. (Appl. Surf. Sci., 2015)

(untitled) - Kumar, P.; Bansiwal, A.; Labhsetwar, N.; Jain, S. L. (Green Chem., 2015)

(untitled) - Hossain, M. N.; Wen, J.; Chen, A. (Sci. Rep., 2017)

(untitled) - Shen, M.; Zhang, L.; Shi, J. (Nanotechnology, 2018)

(untitled) - Zhang, G.; Lan, Z.-A.; Wang, X. (Chem. Sci., 2017)

(untitled) - Wang, X.; Maeda, K.; Thomas, A.; Takanabe, K.; Xin, G.; Carlsson, J. M.; Domen, K.; Antonietti, M. (Nat. Mater., 2009)

(untitled) - Wang, W.; Yu, J. C.; Shen, Z.; Chan, D. K. L.; Gu, T. (Chem. Commun., 2014)

(untitled) - Bandyopadhyay, A.; Ghosh, D.; Kaley, N. M.; Pati, S. K. (J. Phys. Chem. C, 2017)

(untitled) - Hu, J.; Chen, D.; Li, N.; Xu, Q.; Li, H.; He, J.; Lu, J. (Appl. Catal., B, 2018)

(untitled) - Zhang, Q.; Quan, X.; Wang, H.; Chen, S.; Su, Y.; Li, Z. (Sci. Rep., 2017)

(untitled) - Ong, W.-J.; Putri, L. K.; Tan, Y.-C.; Tan, L.-L.; Li, N.; Ng, Y. H.; Wen, X.; Chai, S.-P. (Nano Res., 2017)

(untitled) - Zeng, D.; Wu, P.; Ong, W.-J.; Tang, B.; Wu, M.; Zheng, H.; Chen, Y.; Peng, D.-L. (Appl. Catal., B, 2018)

(untitled) - Kong, Z.; Chen, X.; Ong, W.-J.; Zhao, X.; Li, N. (Appl. Surf. Sci., 2019)

(untitled) - Ong, W.-J. (Front. Mater., 2017)

(untitled) - Chen, X.; Zhao, X.; Kong, Z.; Ong, W.-J.; Li, N. (J. Mater. Chem. A, 2018)

(untitled) - Liao, G.; Chen, S.; Quan, X.; Yu, H.; Zhao, H. (J. Mater. Chem., 2012)

(untitled) - Tang, L.; Jia, C.-t.; Xue, Y.-c.; Li, L.; Wang, A.-q.; Xu, G.; Liu, N.; Wu, M.-h. (Appl. Catal., B, 2017)

(untitled) - Sun, L.; Du, T.; Hu, C.; Chen, J.; Lu, J.; Lu, Z.; Han, H. (ACS Sustainable Chem. Eng., 2017)

(untitled) - Ong, W.-J.; Tan, L.-L.; Chai, S.-P.; Yong, S.-T. (Chem. Commun., 2015)

(untitled) - Rakibuddin, M.; Kim, H.; Ehtisham Khan, M. (Appl. Surf. Sci., 2018)

(untitled) - Xu, J.; Wang, Y.; Zhu, Y. (Langmuir, 2013)

(untitled) - Grzyb, B.; Gryglewicz, S.; Śliwak, A.; Díez, N.; Machnikowski, J.; Gryglewicz, G. (RSC Adv., 2016)

(untitled) - Jiang, Z.; Zhu, C.; Wan, W.; Qian, K.; Xie, J. (J. Mater. Chem. A, 2016)

(untitled) - Huang, H.; Xiao, K.; Tian, N.; Dong, F.; Zhang, T.; Du, X.; Zhang, Y. (J. Mater. Chem. A, 2017)

(untitled) - Wang, H.; Yuan, X.; Wu, Y.; Zeng, G.; Chen, X.; Leng, L.; Li, H. (Appl. Catal., B, 2015)

(untitled) - Rakibuddin, M.; Mandal, S.; Ananthakrishnan, R. (New J. Chem., 2017)

(untitled) - Li, C.-Z.; Wang, Z.-B.; Sui, X.-L.; Zhang, L.-M.; Gu, D.-M. (RSC Adv., 2016)

(untitled) - An, T.; Tang, J.; Zhang, Y.; Quan, Y.; Gong, X.; Al-Enizi, A. M.; Elzatahry, A. A.; Zhang, L.; Zheng, G. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Liu, S.; Zhao, Z.; Wang, Z. (Photochem. Photobiol. Sci., 2007)

(untitled) - Schulte, K. L.; DeSario, P. A.; Gray, K. A. (Appl. Catal., B, 2010)

(untitled) - Iizuka, K.; Wato, T.; Miseki, Y.; Saito, K.; Kudo, A. (J. Am. Chem. Soc., 2011)

(untitled) - Collado, L.; Reynal, A.; Coronado, J. M.; Serrano, D. P.; Durrant, J. R.; de la Peña O'Shea, V. A. (Appl. Catal., B, 2015)

(untitled) - Chen, S.; Pan, B.; Zeng, L.; Luo, S.; Wang, X.; Su, W. (RSC Adv., 2017)

(untitled) - Diercks, C. S.; Liu, Y.; Cordova, K. E.; Yaghi, O. M. (Nat. Mater., 2018)

(untitled) - Di, T.; Zhu, B.; Cheng, B.; Yu, J.; Xu, J. (J. Catal., 2017)

(untitled) - Wang, K.; Li, Q.; Liu, B.; Cheng, B.; Ho, W.; Yu, J. (Appl. Catal., B, 2015)

(untitled) - Li, K.; Peng, B.; Peng, T. (ACS Catal., 2016)

(untitled) - Hummers, W. S., Jr; Offeman, R. E. (J. Am. Chem. Soc., 1958)

(untitled) - Kang, Z.; Tsang, C. H. A.; Wong, N.-B.; Zhang, Z.; Lee, S.-T. (J. Am. Chem. Soc., 2007)

(untitled) - Nash, T. (Biochem. J., 1953)

(untitled) - Hatchard, C. G.; Parker, C. A. (Proc. R. Soc. London, Ser. A, 1956)